2020
DOI: 10.1002/slct.201904492
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Morphology Modification of 5, 5′‐Bisthiazole‐1,1′‐ dioxyhydroxyammonium Salt

Abstract: The growth morphology of 5, 5′‐bisthiazole‐1, 1′‐dioxyhydroxyammonium salt (TKX‐50) under vacuum and solvent conditions was studied by using the attached energy (AE) model .The calculation results show that the (1 1 1) face have large morphological importance in these three additives systems sodium dodecyl sulfonate, sodium dodecyl benzene sulfonate and Tween 20 system, and the predicted TKX‐50 morphology is consistent with the experimental results. Further, the friction sensitivity and impact sensitivity of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…1,1’-dihydroxy-5,5’-tetrazolium dihydroxyamine salt (TKX-50) is a novel high-energy-density compound and one of the most promising third-generation energetic materials. As one of the important properties of explosives, the crystal morphology of TKX-50 has been extensively studied from theoretical simulation [ 62 ] to experiment [ 63 ] and from single component crystal [ 64 ] to co-crystal [ 65 ]. Industrial grade TKX-50 has many shortcomings, such as irregular crystal morphology, small particle size, large aspect ratio, and low intramolecular oxygen content [ 66 ], which affects its application in mixed explosives and propellants.…”
Section: Introductionmentioning
confidence: 99%
“…1,1’-dihydroxy-5,5’-tetrazolium dihydroxyamine salt (TKX-50) is a novel high-energy-density compound and one of the most promising third-generation energetic materials. As one of the important properties of explosives, the crystal morphology of TKX-50 has been extensively studied from theoretical simulation [ 62 ] to experiment [ 63 ] and from single component crystal [ 64 ] to co-crystal [ 65 ]. Industrial grade TKX-50 has many shortcomings, such as irregular crystal morphology, small particle size, large aspect ratio, and low intramolecular oxygen content [ 66 ], which affects its application in mixed explosives and propellants.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the application of morphology prediction models, such as the MAE models, , growth mechanistic model, , and dynamic Monte Carlo simulation method, has become increasing popular. Morphology prediction models have been also widely applied in energetic crystals grown under various conditions, such as vacuum, solvents, and additives, with effects of temperature, volume ratio of mixed solvents, supersaturation, and other conditions covered. Also, this research revealed the growth mechanism of energetic crystals at the microscopic level, which presented theoretical guidance for morphology control. Meanwhile, valid force fields are important for the specified energetic compounds.…”
Section: Application Of Morphology Prediction Methods In Energetic Cr...mentioning
confidence: 99%
“…The morphological dominance surfaces of TKX-50 are summarized as (0 2 0), (1 0 0), (0 1 1), (1 1 0), (1 1 −1) and (1 2 −1). After that, Zhao et al 62 calculated the crystal morphology of TKX-50 in a vacuum using the acoustic emission model and finally determined that the most important part of TKX-50 is the (0 2 0) crystal face (Table 6), which accounts for 48.145% of the total customized surface area. Therefore, the mechanical properties of the (0 2 0) crystal face hold significant importance and serve as a crucial foundation for future explorations into the mechanical behavior of TKX-50.…”
Section: Mechanical Properties Of Tkx-50mentioning
confidence: 99%